Strain sensing behaviour of 3D printed carbon black filled ABS. (October 2018) - Dawoud, Michael; Taha, Iman; Ebeid, Samy J.
Abstract: Carbon Black filled Acrylonitrile Butadiene Styrene (ABS) was used to prepare a polymer composite by Fused Deposition Modeling (FDM) technology. The effect of printing setup on the strain sensing behavior of the composite was investigated, targeting the fabrication of a functionalized composite that is able to detect stress or strain changes in engineering members. Experimental work revealed that internal stresses can be detected based on monitoring the change in resistance as a response to strain. Measurements across sample thickness were found to be most suitable for making general statements about the resistivity of the samples. Hereby, the resistance depends on the intrinsic and the process specific properties of the material. The printing setup was systematically varied in terms of raster angle and gap width. to yield the most sensitive constellation for conductivity The use of a negative gap between the individual rasters in combination with a raster angle of +/−45° was observed to have a positive influence on intensifying the detected signals, making this constellation most sensible for strain sensing applications. Hence, the intrinsic properties of material were enhanced by the adequate selection of processing parameters. This study shows that the functionalized composite can be used as a strain sensor as for health monitoring purposes, to give an example.